Biomass Production of Mangrove Plantation in Sundarbans, West Bengal (India)-a Case Study - Choudhuri, P. K. Roy (Indian Forester, 1991)
This paper deals with biomass productivity of mangrove plantation in the sunderbans (out side the reserve forest). The plantation works were initiated during the year 1982 by social Forestry division of the sunderbans development board as component of the sunderban development project (financed by International Fund for Agriculture Development). The distribution of biomass of different plant components viz. stems, twigs and branches, leaves and roots of different mangrove species in pure form has been discussed. On the basis of utilisable biomass recorded Aycennia spp was higher than Sonnerana apetala Buch-Ham Bruguiera gymnorhiza (L) Lam, Ceriops spp and they wereranked I, II ,III,&IV respectively. Rhlzopora spp are not included in this study as they cover larger surface area by its long spreading stillt roots and spreading umbrella shaped crown. The author concludes that in raising mangrove plantationin sunderban out side reserve forests. Aycennia spp should be the principal species with Bruguiera gymnorhiza, ceriops spp and Sonneritia apetala as quantitative assessment of biomass productivity of Aycennia spp-122.29 MT per ha Sonneratioa apetala 34.51 MT per ha. Bruguiera gymnorhiza 9.48 MT per ha at the age of 5 years and ceriops spp 4.77 per ha at the age of 6 years.